Xenogenic transplantation of human mesenchymal stem cells in a critical size defect of the sheep tibia for bone regeneration - Niemeyer, Philipp; Schönberger, Thomas S.; Hahn, Joachim; Kasten, Philip; Fellenberg, Jörg; Suedkamp, Norbert; Mehlhorn, Alexander T.; Milz, Stefan; Pearce, Simon (Tissue engineering, 2010)
Mesenchymal stem cells (MSCs) represent an attractive cell population for the regeneration of mesenchymal tissues. Their special immunological characteristics suggest that MSCs could be used in nonautologous applications. In this study, the regenerative capacity of human and ovine MSCs was assessed in an ovine critical size defect model. Human and ovine MSCs from bone marrow were cultured on mineralized collagen and implanted into a 3.0-cm-long sheep tibia bone defect (n = 7). Unloaded mineralized collagen served as control. Bone healing was assessed until euthanasia 26 weeks after surgery by radiology and histologically after euthanasia. The presence of human cells after xenogenic transplantation was analyzed using human-specific in situ hybridization. Both radiology and histology demonstrated significantly better bone formation after transplantation of autologous ovine MSCs on mineralized collagen compared with unloaded matrices and with the xenogenic treatment group. Nevertheless, no local or systemic rejection reactions could be observed after transplantation of human MSCs, although the presence of human MSCs could be demonstrated. It can be concluded that despite successful demonstration of the presence of human MSCs after xenogenic transplantation, the xenogenic transplantation of human MSCs leads to poorer bone regeneration than autologous transplantation of ovine MSCs.